2010
DOI: 10.1016/j.mito.2010.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial fission/fusion dynamics and apoptosis

Abstract: Mitochondria play an important role in the progression of apoptosis through the release of pro-apoptotic factors, such as cytochrome c, from the mitochondrial intermembrane space.During this process, mitochondrial networks are dramatically reorganised from long filamentous interconnected tubules into small punctate spheres. Whether remodelling of mitochondrial networks is necessary for apoptosis-associated cytochrome c release, or merely an accompanying process, has been a subject of debate. Here we discuss ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
153
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(161 citation statements)
references
References 112 publications
6
153
1
1
Order By: Relevance
“…The mitochondria are most dynamic organelles frequently involved in the process of fusion and fission forming an interconnecting tubular network and also individual entity (49). However, during apoptosis, mitochondria undergo fragmentation, which results in enhanced accumulation of smaller mitochondria (49). We have observed that Drp-1 significantly involved in regulating the mitochondrial shape, their fragmentation, and also functions.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The mitochondria are most dynamic organelles frequently involved in the process of fusion and fission forming an interconnecting tubular network and also individual entity (49). However, during apoptosis, mitochondria undergo fragmentation, which results in enhanced accumulation of smaller mitochondria (49). We have observed that Drp-1 significantly involved in regulating the mitochondrial shape, their fragmentation, and also functions.…”
Section: Discussionmentioning
confidence: 87%
“…The impaired mitochondrial dynamics was associated with the increase in the levels of Drp-1 with insignificant changes in other mitochondrial dynamin-related proteins. The mitochondria are most dynamic organelles frequently involved in the process of fusion and fission forming an interconnecting tubular network and also individual entity (49). However, during apoptosis, mitochondria undergo fragmentation, which results in enhanced accumulation of smaller mitochondria (49).…”
Section: Discussionmentioning
confidence: 99%
“…Neurons are especially sensitive to imbalances in the axonal mitochondrial transport process as both energy supply and calcium handling are vital at the synapse [8]. At the other extreme, excessive stress generally results in mitochondrial fragmentation and formation of small, punctate mitochondria and ultimately, apoptosis if the cell is too damaged [89,90].…”
Section: Hormesis In Action-mitochondrial Networkmentioning
confidence: 99%
“…Fusion of both membranes is a two-step process that occurs in a coordinate fashion, although the precise mechanism remains unclear (Malka, Guillery et al, 2005). Mitochondrial fission requires the recruitment of dynamin-related protein 1 (Drp1) from the cytosol to the OMM where it forms multimeric rings and spiral-like structures that surround and constrict the organelle in a GTP-dependent manner (Sheridan & Martin, 2010). The mechanism that triggers this recruitment is still unknown, however, Fis1, a small mitochondrial transmembrane protein, seems to be responsible for this mobilization (Sheridan & Martin, 2010).…”
mentioning
confidence: 99%
“…Mitochondrial fission requires the recruitment of dynamin-related protein 1 (Drp1) from the cytosol to the OMM where it forms multimeric rings and spiral-like structures that surround and constrict the organelle in a GTP-dependent manner (Sheridan & Martin, 2010). The mechanism that triggers this recruitment is still unknown, however, Fis1, a small mitochondrial transmembrane protein, seems to be responsible for this mobilization (Sheridan & Martin, 2010). Mitochondria are the only organelles outside of the nucleus that contain their own genome and replicate itself in an independent manner from the nuclear genome.…”
mentioning
confidence: 99%